Supply and Demand Shocks and the Growth of the Brazilian Agriculture - Camargo Barros, Geraldo Sant'Ana
Shocks de oferta y demanda y el crecimiento de la Agricultura Brasilera
Keywords: BRASIL; MERCADO BURSATIL; OFERTA Y DEMANDA